PENGARUH KAJIAN EMBRIOLOGI TERHADAP PERUBAHAN MAKNA KATA ALAQOH DALAM QUR’AN TERJEMAH KEMENAG RI: ANALISIS HERMENEUTIKA GADAMER - Kholifah Rahmawati (TAFASIR: Journal of Quranic Studies, 2025)
This research examines the semantic shift of the term alaqah in the latest Indonesian Ministry of Religious Affairs Qur’an translation, from “a clot of blood” to “something that clings.” The change is influenced by modern embryological studies which reveal that in the alaqah phase, the embryo contains no blood elements but is instead attached to the uterine wall. Although classical tafsir interprets alaqah as blood-like, the new translation adopts a scientific perspective. Using Gadamer’s Hermeneutics, particularly Fusion of Horizons and Aesthetic Critique, this study argues that the newer meaning reflects modern epistemic taste shaped by rational-empirical paradigms rather than classical exegetical tradition.